2017
DOI: 10.1001/jamaophthalmol.2017.3151
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Intraocular Pressure by Patients With Glaucoma

Abstract: The ability of patients to measure their own intraocular pressure (IOP) would allow more frequent measurements and better appreciation of peak IOP and IOP fluctuation.OBJECTIVE To examine whether patients with glaucoma can perform self-tonometry using a rebound tonometer and examine patient acceptability. DESIGN, SETTING, AND PARTICIPANTS An observational study in which IOP was assessed using Goldmann applanation tonometry and a rebound tonometer. Consecutive patients were provided with a patient information s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 18 publications
9
47
0
Order By: Relevance
“… 31 Pronin et al reported that the IOP difference was −2.5 mmHg (95% LOA was between −4.71 and 9.88 mmHg) with self-measurement and −2.6 mmHg (95% LOA was between −3.48 and 8.8 mmHg) with measurement by a second party compared to GAT. 32 Mudie et al reported that the IOP difference between GAT was −0.33 mmHg (95% LOA was unclear) with self-measurement. 33 Only Takagi et al reported that the IOP difference between GAT was 0.70 mmHg (95% LOA was between −3.07 and 4.46 mmHg) with self-measurement and 0.91 mmHg (95% LOA was between −2.75 and 4.56 mmHg) as measured by a second party.…”
Section: The Characteristics Of Each Device and Iop Valuesmentioning
confidence: 99%
“… 31 Pronin et al reported that the IOP difference was −2.5 mmHg (95% LOA was between −4.71 and 9.88 mmHg) with self-measurement and −2.6 mmHg (95% LOA was between −3.48 and 8.8 mmHg) with measurement by a second party compared to GAT. 32 Mudie et al reported that the IOP difference between GAT was −0.33 mmHg (95% LOA was unclear) with self-measurement. 33 Only Takagi et al reported that the IOP difference between GAT was 0.70 mmHg (95% LOA was between −3.07 and 4.46 mmHg) with self-measurement and 0.91 mmHg (95% LOA was between −2.75 and 4.56 mmHg) as measured by a second party.…”
Section: The Characteristics Of Each Device and Iop Valuesmentioning
confidence: 99%
“…12 No anesthesia or calibration was required during the procedure. 13 The iCare tonometer uses a P value to indicate the quality of the measurement taken, and we discarded any iCare reading with an error bar.…”
Section: Subjectsmentioning
confidence: 99%
“…IOP measurements with the Icare HOME tonometer were within 5 mm Hg of the GAT measurements. The Icare measurements, however, were consistently lower than the GAT measurements, especially in the lower IOP ranges [30].…”
Section: Self-tonometry/home-tonometrymentioning
confidence: 68%